Lab-NMDAR: simulators of NMDA receptor’s basic electrophysiology - Reyes Monreal, Marleni; Pérez Bonilla, María Eugenia; Quintero Pérez, Jessica; Reyes Lazalde, Arturo; Flores Hernández, Jorge (Acta Universitaria, 2022)
The development of educational software that allows the implementation of laboratory practices is necessary. This paper presents the design and development of the Lab-NMDAR program, consisting of three simulators for the teaching-learning of NMDA receptor electrophysiology: (1) NMDAR-Blocking Mg2+ simulator, (2) NMDAR-Glycine simulator, and (3) single channel NMDA-Blocking Mg2+ simulator. The program was implemented in Visual Basic® for Windows® environment. With these simulators the student knows the NMDA current, reproduces its dependence on voltage, simulates its blocking by magnesium in macroscopic current recordings and in a single channel, determines the involvement of NMDA and glycine in NMDA receptor activation and produces virtual dose-response experiments. The program is easy to use, it runs on a personal computer with minimal resources.